Peningkatan Mutu Kompetensi lulusan Melalui Pembiasaan Kegiatan Keagamaan dan Keterampilan - Ali Masyharudin, Rofiatul Hosna (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2021)
In order for education to form a good quality of graduate competence and to give birth to a generation with character, the quality of education must be considered. Not only limited to adding lesson hours, but educational programs can be integrated with other subject matter, Permendikbud, curriculum and school characteristics. Thus, the formulation of the problem can be taken as follows (1) What is the scope of improving the quality of competence of graduates through religious and skill activities at SMA Islam Sunan Ampel Seblak? (2). How to improve the quality of graduate competencies through religious activities at SMA Islam Sunan Ampel Seblak? (3). How to improve the quality of graduate competencies through skill activities at SMA Islam Sunan Ampel Seblak? (4). What are the supporting and inhibiting factors for improving the quality of graduate competencies through religious and skill activities at SMA Islam Sunan Ampel Seblak? This study used a qualitative approach. In this study using the method of observation, interviews and documentation. The results obtained from research at SMA Islam Sunan Ampel Seblak can be concluded that there is an effort to improve the quality of graduate competence through religious activities and skills applied at SMA Islam Sunan Ampel Seblak, namely: (1) integrated with other subject matter, Permendikbud, curriculum and school characteristics, (2) school culture, (3) religious activities (4) skills activities. By collaborating the three models, the quality of graduates has the character of being religious people, having good character and having an entrepreneurial spirit who is able to face the challenges of the era of technology 5.0 based on the al-Qur'an and hadits.